Fear is the Path to the Dark Side: Unsafe Delivery, One of the Consequences of Fear of the SARS-CoV-2 Pandemic, A Case Report. Issue 4 (8th October 2021) - Nieto-Calvache, Albaro José; Padilla, Iván; Tabares-Blanco, Mario Fernando; López-Girón, María Camila; Vergara Galliadi, Lina María
Abstract : Abstract: Indirect effects of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic are difficult to calculate. Fear of intrahospital infection has led to a decrease in the use of emergency services and the performance of elective procedures. Several low- and middle-income countries have seen the number of institutional deliveries reduced, even in the absence of a follow-up program for home births. We present the case of a patient with adequate prenatal care and an institutional delivery plan who, due to the SARS-CoV-2 pandemic, chose to have a home delivery with unsafe conditions. The lack of supervision by health personnel and the absence of an immediate consultation plan facilitated the presentation of postpartum hemorrhage and poor neonatal results. Little attention has been paid during the pandemic to pregnant women who decide to have their birth at home. A broad discussion is necessary in this regard, to regain the confidence of the population and strengthen institutional births, or to strengthen midwife-assisted home births programs. Patients' fear to acquiring SARS-CoV-2 infection inside hospitals is a factor that must be taken into account in prenatal care programs.